Enhancing Self-Mastery in Low-Achieving Students Through Islamic Education: Perspective of Carl Rogers' Self Theory - Prasetyo, Eko Agus; Alfiyaturohmaniyyah, Shicha; Sa'diyah, Elok Halimatus (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
Students with low achievement often face challenges in developing self-mastery, including low motivation, lack of self-confidence, and difficulty managing emotions. This study aims to identify factors that influence the development of self-mastery in students and understand the role of teachers based on Carl Rogers' self theory. The method used is a qualitative approach conducted through a case study at SD Islam Hasanudin 04 Semarang with a thematic analysis approach data analysis technique. The data obtained were the results of interviews with teachers, field observations, and school documents. The results of the study indicate that (1) self-mastery is influenced by internal factors such as self-motivation and emotional management, and (2) external factors such as family and teacher support. (3) Positive family support and constructive feedback from teachers have been shown to increase students' self-confidence, encourage mental resilience, and intrinsic motivation. (4) This study also found criteria for teachers who can improve students' self-mastery. This study provides important insights into how environmental influences and teacher interventions can help low-achieving students reach their maximum potential